Я познаю мир: Философия: детская энциклопедия / авт.-сост. В. Д. Губин - Губин В. Д. (Я познаю мир, 1998)
Экземпляры: ф.15 (20150305) / Инвентарный номер: 56325 / Цена: / Сис.шифр: 87.3я2 / Авт.знак: Я 11 / ГРНТИ: 02 / ББК: 87.3я2